Finding Makhubu: A morphological forensic facial comparison. (April 2018) - Houlton, T.M.R.; Steyn, M.
Highlights: Soweto Youth Student Uprising hero, Mbuyisa Makhubu, has been missing since 1978. Victor Vinnetou illegally entered Canada in 1988 and is evasive about his identity. Vinnetou is believed to be Makhubu, but a performed DNA test was inconclusive. A morphological facial comparison utilised SAPS protocol and FISWG guidelines. The result was inconclusive, but does not dismiss Vinnetou from being Makhubu. Abstract: June 16, 1976, marks the Soweto Youth Student Uprising in South Africa. A harrowing image capturing police brutality from that day comprises of 18-year-old Mbuyisa Makhubu carrying a dying 12-year-old Hector Peterson. This circulated international press and contributed to world pressure against the apartheid government. This elevated Makhubu's profile with the national security police and forced him to flee to Botswana, then Nigeria, before disappearing in 1978. In 1988, Victor Vinnetou illegally entered Canada and was later arrested on immigration charges in 2004. Evasive of his true identity, the Canadian Border Services Agency and Makhubu's family believe Vinnetou is Makhubu, linking them by a characteristic moon-shaped birthmark on his left chest. A performed DNA test however, was inconclusive. Following the continued 40-year mystery, Eye Witness News in 2016 requested further investigation. Using a limited series of portrait images, a forensic facial comparison (FFC) was conducted utilising South African Police Service (SAPS) protocols and Facial Identification Scientific Working Group (FISWG) guidelines. The images provided, presented a substantial time-lapse and generally low resolution, while being taken from irregular angles and distances, with different subject poses, orientations and environments. This enforced the use of a morphological analysis; a primary method of FFC that develops conclusions based on subjective observations. The results were fundamentally inconclusive, but multiple similarities and valid explanations for visible differences were identified. To enhance the investigation, visual evidence of the moon-shaped birthmark and further DNA analysis is required.